THE EFFECT OF CORPORATE GOVERNANCE ON TAX AVOIDANCE WITH CORPORATE SOCIAL RESPONSIBILITY AS MEDIATION - Widijaya; Fitri Lianty (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. This research was conducted to analyze the relationship between corporate governance and tax avoidance, mediated by corporate social responsibility. Tax avoidance is the dependent variable measured by the effective tax rate (ETR), while corporate governance is the independent variable measured by the Corporate Governance Index (CGI-score). The mediating variable in this study is corporate social responsibility. The study also includes control variables such as firm size, return on asset, and leverage. This research sample is based on a sample of Indonesian companies listed on the Indonesian Stock Exchange (IDX) for the period 2017-2021. The survey sample that meets the criteria includes 60 companies with a total of 300 observational data collections. Research results show that corporate governance has a significant impact on tax avoidance, corporate governance has no significant impact on corporate social responsibility, corporate social responsibility has no significant impact on tax avoidance and corporate social responsibility is not able to mediate corporate governance and tax avoidance. Abstrak. Penelitian ini dilakukan untuk menganalisis hubungan antara corporate governance dengan penghindaran pajak yang dimediasi oleh tanggung jawab sosial perusahaan. Penghindaran pajak adalah variabel dependen yang diukur dengan tarif pajak efektif (ETR), sedangkan tata kelola perusahaan adalah variabel independen yang diukur dengan Corporate Governance Index (CGI-score). Variabel mediasi dalam penelitian ini adalah tanggung jawab sosial perusahaan. Penelitian ini juga memasukkan variabel kontrol seperti ukuran perusahaan, return on asset, dan leverage. Sampel penelitian ini berdasarkan sampel perusahaan Indonesia yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2021. Sampel survei yang memenuhi kriteria meliputi 60 perusahaan dengan total 300 koleksi data observasi. Hasil penelitian menunjukkan bahwa corporate governance berpengaruh signifikan terhadap tax avoidance, corporate governance tidak berpengaruh signifikan terhadap corporate social responsibility, corporate social responsibility tidak berpengaruh signifikan terhadap tax avoidance dan corporate social responsibility tidak mampu memediasi corporate governance dan tax avoidance.